Find $\lim\limits_{x\to\infty}\left(\frac{a_1}{a_0S_1}+\frac{a_2}{S_1S_2}+...+\frac{a_n}{S_{n-1}S_n}\right)$ where $n=0,1,2,...$ and $a_n=2015^n,S_n=\sum\limits_{k=0}^{n}a_k$

$S_n$ can be written as the geometric sum $S_n=\frac{2015^{n+1}-1}{2014}$.

Applying the values for $a_k$ and $S_k$ can't give a closed form in the limit.

How to transform sequence in the limit so it gives closed form (if possible)?

  • 2
    $\begingroup$ May be your Question is $$\lim\limits_{n\to\infty}\left(\frac{a_1}{S_0S_1}+\frac{a_2}{S_1S_2}+...+\frac{a_n}{S_{n-1}S_n}\right)$$ $\endgroup$ – juantheron Sep 18 '15 at 17:35
  • 5
    $\begingroup$ Try to exploit $a_{n}=S_n-S_{n-1}$ to get a telescopic sum. $\endgroup$ – Jack D'Aurizio Sep 18 '15 at 17:37
  • $\begingroup$ No. It seems that would simplify this. $\endgroup$ – user300045 Sep 18 '15 at 17:38
  • $\begingroup$ @Jack D'Aurizio I can't get to the telescopic sum. $\frac{a_1}{a_0S_1}+\sum\limits_{k=2}^{n}\left(\frac{S_k}{S_{k-1}S_k}-\frac{S_{k-1}}{S_{k-1}S_k} \right)$. $\endgroup$ – user300045 Sep 18 '15 at 18:38

Since $$S_{n}=\sum_{k=0}^n2015^k=\sum_{k=0}^{n-1}2015^k+2015^n=S_{n-1}+2015^n\qquad n\ge 1$$ it follows \begin{align} \frac{a_n}{S_{n-1}S_n}&=\frac{2015^n}{S_{n-1}(S_{n-1}+2015^n)}\\ &=\frac{S_{n-1}+2015^n-S_{n-1}}{S_{n-1}(S_{n-1}+2015^n)}\\ &=\frac{1}{S_{n-1}}-\frac{1}{S_{n-1}+2015^n}\\ &=\frac{1}{S_{n-1}}-\frac{1}{S_n} \end{align} Thus $$\sum_{k=0}^n\frac{a_k}{S_{k-1}S_k}=\underbrace{\left(\frac{1}{S_0}-\frac{1}{S_1}\right)+\left(\frac{1}{S_1}-\frac{1}{S_2}\right)+\ldots+\left(\frac{1}{S_{n-1}}-\frac{1}{S_n}\right)}_{n\text{ terms}}=\frac{1}{S_0}-\frac{1}{S_n}$$ \begin{align} \lim_{n\to\infty}\sum_{k=0}^n\frac{a_k}{S_{k-1}S_k}&=\lim_{n\to\infty}\left(\frac{1}{S_0}-\frac{1}{S_n}\right) \end{align}

| cite | improve this answer | |
  • $\begingroup$ I have to say the first lines are quite irrelevant, the telescopic sum just follows from $a_k= S_k-S_{k-1}$, no matter if $S_k$ has some nice closed form or not, we just need $S_n\to +\infty$ as $n\to +\infty$. $\endgroup$ – Jack D'Aurizio Sep 18 '15 at 20:24

Since $a_k = S_k - S_{k - 1}$ we easily deduce that $$\frac {a_k} {S_{k - 1} S_k} = \frac {1} {S_{k - 1}} - \frac {1} {S_k}.$$ Then, $$\lim_{n \to \infty} \sum_{k = 1}^{n} \frac {a_k} {S_{k - 1} S_k} = \lim_{n \to \infty} \left(\frac {1} {S_0} - \frac {1} {S_n} \right) = \frac {1} {S_0},$$ which I take to be $1$.

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.